Gender, Agricultural Commercialization, and Collective Action in Kenya - Elisabeth Fischer; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2012)
With the commercialization of agriculture, women are increasingly disadvantaged because of persistent gender-disparities in access to productive resources. Farmer collective action that intends to improve smallholder access to markets and technology could potentially accelerate this trend. Here, we use survey data of small-scale banana producers in Kenya to investigate the gender implications of recently established farmer groups. Traditionally, banana has been a women's crop in Kenya. Our results confirm that the groups contribute to increasing male control over banana. While male control over banana revenues does not affect household food security, it has a negative marginal effect on dietary quality. We demonstrate that the negative gender implications of farmer groups can be reduced or avoided when women are group members themselves. In the poorest income segments, group membership even seems to have a positive effect on female-controlled income share. Some policy implications towards gender mainstreaming of farmer collective action are discussed.
Keywords: D71; J16; O12; O13; O31; Q13; 330; gender; collective action; market access; agricultural technology; household food security and nutrition; Kenya